2015
DOI: 10.2967/jnmt.115.156844
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT Assessment of Infected Intracardiac Devices With and Without Attenuation Correction

Abstract: Left ventricular assist devices (LVADs) provide the ability to maintain cardiac output and sustain life as a bridge to transplantation, definitive therapy, or a permanent decision. We present a case of LVAD drive infection that was differentiated from pump infection by the use of attenuation-corrected and non-attenuationcorrected CT, along with correlation with the planar images. Clinically, the patient was suspected of having infection; however, the clinician did not know which components of the device were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Computed tomography (CT) scanning is of limited utility due to the reflective properties of the pump body. However positron emission tomography (PET-CT) [64]; or gallium single photon emission computed tomography (SPECT-CT) [64][65][66], reviewed in [40]) have been used to diagnose infection of LVAD components as well as to assess for metastatic sites of infection often found with prolonged bacteremia with pathogens such as S. aureus and P. aeruginosa (reviewed in [40,67,68]). Erba et al [69] showed that 99m Tc-hexamethypropylene amine oxime labeled autologous white blood cell ( 99m Tc-HMPAO-WBC) SPECT-CT had 94% sensitivity at detecting cardiac implantable electronic device infections, with 95% negative predictive value in patients with other sources of infection.…”
Section: Diagnosis Of Lvad Infectionsmentioning
confidence: 99%
“…Computed tomography (CT) scanning is of limited utility due to the reflective properties of the pump body. However positron emission tomography (PET-CT) [64]; or gallium single photon emission computed tomography (SPECT-CT) [64][65][66], reviewed in [40]) have been used to diagnose infection of LVAD components as well as to assess for metastatic sites of infection often found with prolonged bacteremia with pathogens such as S. aureus and P. aeruginosa (reviewed in [40,67,68]). Erba et al [69] showed that 99m Tc-hexamethypropylene amine oxime labeled autologous white blood cell ( 99m Tc-HMPAO-WBC) SPECT-CT had 94% sensitivity at detecting cardiac implantable electronic device infections, with 95% negative predictive value in patients with other sources of infection.…”
Section: Diagnosis Of Lvad Infectionsmentioning
confidence: 99%